Risk factors for seizures after cranioplasty. (March 2019) - Shih, Fu-Yuan; Lin, Chia-Cheng; Wang, Hung-Chen; Ho, Jih-Tsun; Lin, Chih-Hsiang; Lu, Yan-Ting; Chen, Wu-Fu; Tsai, Meng-Han
Highlights: Seizures (30.3%) are the most common complication after cranioplasty. Delayed cranioplasty is associated with early post-cranioplasty seizures. Presence of neurological deficit is a risk factor for late post-cranioplasty seizures. Abstract: Purpose: Cranioplasty can improve a patient's psychosocial and cognitive functions after decompressive craniectomy, however seizures are a common complication after cranioplasty. The risk factors for early and late seizures after cranioplasty are unclear. This study is to evaluate the risk factors for early and late seizure after cranioplasty. Methods: Two hundred and thirty-eight patients who received cranioplasty following craniectomy between January 2012 and December 2014 were included in this study. The risk factors of the patients with early and late post-cranioplasty seizures were compared to those with no post-cranioplasty seizures. Results: Seizures (73/238, 30.3%) were the most common complication after cranioplasty. Of these 73 patients, 17 (7.1%) had early post-cranioplasty seizures and 56 (23.5%) had late post-cranioplasty seizures. Early post-cranioplasty seizures were related to a longer interval between craniectomy and cranioplasty (P = 0.006), artificial materials (P < 0.001), and patients with late post-craniectomy seizures (P = 0.001). Late post-cranioplasty seizures were related to the presence of neurological deficits (P = 0.042). After stepwise logistic regression analysis, a longer interval between craniectomy and cranioplasty (P = 0.012; OR: 1.004, 95% CI: 1.001–1.007) and late post-craniectomy seizures (P = 0.033; OR: 4.335, 95% CI: 1.127–16.675) were independently associated with early post-cranioplasty seizures. Conclusion: Delayed cranioplasty procedures and seizures before cranioplasty were significantly associated with early post-cranioplasty seizures. Further studies are warranted to investigate whether early surgery after craniectomy can reduce the risk of early post-cranioplasty seizures.